PENGARUH KEPUTUSAN KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABELMODERATING - Stella Butje; Cepi Pahlevi; Erlina Pakki (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
The value of the company is affected by a number of internal factors of the company where these factors are often used by potential investors in assessing the company's ability in an attempt to increase the value of the company. This study aims to provide empirical evidence on the influence of dividend policy, debt policy and investment policy on the value of manufacturing companies of various industry sub-sector listed in Indonesia Stock Exchange period 2012-2016. To test and provide empirical evidence on whether profitability can moderate the effect of dividend policy, debt policy and investment policy on the value of manufacturing companies of various industry sub-sectors listed in Indonesia Stock Exchange period 2012-2016. The result of empirical analysis that dividend policy have positive and significant effect to company value. Debt policy (DER) has a positive and significant impact on company value. Investment policy has a positive and significant effect on company value. Interaction test found that profitability can not moderate the influence of dividend policy to firm value. Interaction test results obtained findings that profitability can moderate the influence between debt policy to profitability and profitability can not moderate the influence of investment policy on the value of manufacturing companies’ sub-sector miscellaneous industries listed in Indonesia Stock Exchange 2012-2016.